Formação continuada de professores de uma escola pública estadual, visando a inserção das TIC em sala de aula - Lima, Ana Paula Santos de (2019)
This research was conducted between 2015 and 2018 in a state public school in the city of Santa Maria / RS and had the participation of teachers and students in this school. The aim of the study was to analyze the possible contributions of a continued teacher education program using ICT as part of the teaching strategy. Characterized as qualitative research, with exploratory objective in a collaborative research format, the study provided the opportunity to write three scientific manuscripts. The first one deals with "Study of the teacher’s profile and the technologies employed in the classroom in a public state school in the city of Santa Maria / RS", the second manuscript "Importance of continued education in teaching pedagogical praxis for the use of technologies: a necessary space", and the third named, "Encouraging student leadership through a training program for insertion of ICT in the classroom." We identified that the teachers, being the co-authors of the process, presented greater commitment regarding their participation and, although it was not the object of this research, creativity occurred to innovate their own classroom practice with the development of new proposals. The measured results allow us to build the following statements: for teacher education processes, it is necessary to plan for the long term, so that there is a time between the new skills developed with the use of ICT and the effective introspection by the teacher. The training developed expanded the use and frequency of ICT by teachers, and all participants began to incorporate technologies as classroom tools. Based on the teacher training strategy we can state that there have been changes in the behavior of teaching professionals and a reflection on the practice. With the new skills developed, the process of use and the portfolio of ICT used deepened to greater levels of complexity and expanded the technologies used. Finally, there was a role for students, from the training, where they began to use ICT for research, work development and see themselves as co-participants in the process of expanding learning opportunities, suggesting other technologies and approaches. We conclude that if there is a pragmatic way of improving the quality of teaching through teacher training, this same path can still bring with it new educational practices, as well as enabling a greater protagonism of the student in his role as an apprentice. It bring together the opportunity of a school that starts to develop a culture of research on technology support. This study, therefore, has brought relevance to the area of research on teacher education and the use of ICT by offering a perspective from which other researchers can broaden further studies to improve this proposal as well as reproduce it in other schools.